1993
DOI: 10.1042/bj2900801
|View full text |Cite
|
Sign up to set email alerts
|

Expression and partial characterization of a cathepsin B-like enzyme (Sm31) and a proposed ‘haemoglobinase’ (Sm32) from Schistosoma mansoni

Abstract: Schistosoma mansoni protein Sm31 is a cysteine proteinase similar to mammalian lysosomal cathepsin B, proposed to be a key enzyme in schistosome metabolism. Protein Sm32 has been identified as a putative cysteine proteinase termed a ‘haemoglobinase’. Since neither Sm31 nor Sm32 have been completely purified, some controversy of the nature of the ‘true’ digestive enzyme still exists. By incubating a radiolabelled cysteine-proteinase active-site-directed synthetic inhibitor with total S. mansoni proteins, the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 29 publications
(24 reference statements)
1
20
0
Order By: Relevance
“…VPEs are classified as a novel family of cysteine proteinase. The plant VPEs exhibit homology to a putative cysteine proteinase, Sm32, of the human parasite Schistosoma mansoni [7,21]. However, the physiological function of the Schistosoma enzyme is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…VPEs are classified as a novel family of cysteine proteinase. The plant VPEs exhibit homology to a putative cysteine proteinase, Sm32, of the human parasite Schistosoma mansoni [7,21]. However, the physiological function of the Schistosoma enzyme is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Clostripain probably does not form specific S' subsite loops as found in common serine proteases (Schellenberger et al, 1993a). Gilles et al (1984), and Gotz and Klinkert (1993) stated that the primary structure of clostripain is not homologous with either other cysteine proteases or with any other known protein structure. The outstanding behaviour in forming peptide bonds with proline in the P: position underlines how extraordinary this enzyme is and indicates that hydrogen bonds are not significantly involved in the binding of the nucleophile and the enzyme subsite.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that proteolysis and/or autolysis around the asparagine residue induces a conformational change in the inactive precursor and then generates an active vacuolar processing enzyme in vivo and in E. coli transformed with pVPEdel. Gotz and Klinkert (1993) reported that insect cells expressing the complete cDNA sequence of the putative cysteine proteinase of the human parasite S. mansoni has no proteolytib activity on hemoglobin. They suggested that the expressed protein is not further cleaved to produce an active form.…”
Section: Discussionmentioning
confidence: 99%